2015
DOI: 10.2967/jnumed.115.160085
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Validation of the Automated Bone Scan Index as an Imaging Biomarker to Standardize Quantitative Changes in Bone Scans of Patients with Metastatic Prostate Cancer

Abstract: A reproducible and quantitative imaging biomarker is needed to standardize the evaluation of changes in bone scans of prostate cancer patients with skeletal metastasis. We performed a series of analytic validation studies to evaluate the performance of the automated bone scan index (BSI) as an imaging biomarker in patients with metastatic prostate cancer. Methods Three separate analytic studies were performed to evaluate the accuracy, precision, and reproducibility of the automated BSI. Simulation study: bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…Additionally, the centralized visual assessment of a bone scan, in a multisite study, does not account for the deviations from the bone scan procedure guidelines. Recently, in the analytic validation study of automated BSI, we have demonstrated that with minimal manual supervision the automated BSI can minimize the interoperator variability in assessing change in bone scans (7). In this preanalytical study, we have identified scanning speed and the resulting image counts as a procedural factor in bone scan image acquisition that can affect the reproducibility and accuracy of automated BSI assessment and therefore needs subsequent standardization for prospective clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the centralized visual assessment of a bone scan, in a multisite study, does not account for the deviations from the bone scan procedure guidelines. Recently, in the analytic validation study of automated BSI, we have demonstrated that with minimal manual supervision the automated BSI can minimize the interoperator variability in assessing change in bone scans (7). In this preanalytical study, we have identified scanning speed and the resulting image counts as a procedural factor in bone scan image acquisition that can affect the reproducibility and accuracy of automated BSI assessment and therefore needs subsequent standardization for prospective clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the computer automation, the time of detecting metastatic lesion and calculating the BSI was reduced to 3-5 s per scan. The recent analytic validation study of automated BSI demonstrated that the platform has consistent accuracy in low-to high-burden disease and that with minimal manual supervision the automated BSI can minimize the interoperator variability (6,7). The analytic validation study was a vital step forward in the continual effort to validate automated BSI as an imaging biomarker in patients with metastatic prostate cancer.…”
mentioning
confidence: 99%
“…The understanding of BSI ranges and bone imaging patterns are convenient to standardize the perception of disease severity and therapeutic changes when patients are referred to or from other hospitals. Analytical validation with a revised algorithm showed the linearity of automated BSI with simulated phantom BSI including ranges of BSI >10% …”
Section: Bsi and Extent Of Bone Metastasismentioning
confidence: 99%
“…Analytical validation with a revised algorithm showed the linearity of automated BSI with simulated phantom BSI including ranges of BSI >10%. 15…”
Section: Bsi and Extent Of Bone Metastasismentioning
confidence: 99%
“…Since the automated bone scan index (BSI) is a quantitative parameter, the comments on qualitative assessments are inapplicable. Our analytic validation study demonstrated the validity of the automated BSI with a Pearson r of 0.99 (P , 0.0001) and with associated parameters of linear regression (slope, 0.80 [95% confidence interval, 0.78-0.83]; intercept, 0.38 [95% confidence interval, 0.25-0.51]) (2). In this study, Cohen k-agreement and other well-known standard tests for imaging biomarkers (3) were also used to evaluate the reliability of the automated BSI platform.…”
Section: Siamak Sabourmentioning
confidence: 99%